Case report: Documentation of cutaneous only pemphigus vulgaris without history of mucosal lesions in North America - Baker, John; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2022)
Background. Pemphigus is a group of autoimmune blistering diseases including Pemphigus vulgaris (PV) and Pemphigus foliaceus (PF). These conditions exhibit lesions with mucosal or mucocutaneous PV or, cutaneous morphology PF, respectively, as framed by the Desmoglein Compensation Hypothesis (DCH). However, some PV patients present with solely cutaneous disease (cPV), and growing evidence suggests the existence of a cPV subtype without any history of mucosal erosions/blisters (cPVwohm), neither of which are predicted by the DCH. Methods. Participants were recruited from several outpatient clinical settings and patient support group meetings throughout the US. On intake, subjects provided blood samples and completed questionnaires regarding their disease status. Results. We report three cases of clinically and histologically confirmed cPV without history of mucosal lesions (cPVwohm). Of these patients, two do not carry the most common PV associated HLA alleles, DRB1*0402 or DQB1*0503. The same two patients also tested negative for the primary PV associated autoantibodies, anti-desmoglein 3 and anti-desmoglein 1, while in active disease status. Conclusion: We confirm the first documented individual cases of cPVwohm in North America, supporting the existence of PV patients that develop cutaneous disease without a history of mucosal lesions, challenging the fidelity of the DCH. Two of the 3 patients reported did not type for the common PV-associated HLA genes or display anti-desmoglein autoantibodies while in active disease, suggesting cPV patients may develop Pemphigus via genetic and immune mechanisms that differ from typical mucosal or mucocutaneous PV.